2013
DOI: 10.1016/j.foodchem.2013.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food formulation and thermal processing on flavones in celery and chamomile

Abstract: Flavones isolated from celery varied in their stability and susceptibility to deglycosylation during thermal processing at pH 3, 5, or 7. Apigenin 7-O-apiosylglucoside was converted to apigenin 7-O-glucoside when heated at pH 3 and 100 °C. Apigenin 7-O-glucoside showed little conversion or degradation at any pH after 5 h at 100 °C. Apigenin, luteolin, and chrysoeriol were most stable at pH 3 but progressively degraded at pH 5 or 7. Chamomile and celery were used to test the effects of glycosidase-rich foods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…15,16 A previous report indicated that apigenin-7-O-glucoside can be enzymatically hydrolyzed to produce apigenin through β-glucosidase. 17,18 However, the metabolic mechanism of luteolin and luteolin-7-O-glucoside production is not entirely understood. In the present study, we first uncover that the flower of D. morifolium is a rich source of luteolin and luteolin-7-Oglucoside.…”
Section: ■ Introductionmentioning
confidence: 99%
“…15,16 A previous report indicated that apigenin-7-O-glucoside can be enzymatically hydrolyzed to produce apigenin through β-glucosidase. 17,18 However, the metabolic mechanism of luteolin and luteolin-7-O-glucoside production is not entirely understood. In the present study, we first uncover that the flower of D. morifolium is a rich source of luteolin and luteolin-7-Oglucoside.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3). Thermal treatment during boiling or roasting can lead to the cleavage of the aglycone of flavonoids during ethnomedical practice [16]. Other components in herbal mixtures with β glucosidase activity [17] can also cause this decomposition, as well as enzymatic hydrolysis in skin tissue during topical application [18].…”
Section: Resultsmentioning
confidence: 99%
“…The phytochemical studies had confirmed myricetin-3-O-rhamnoside as the main constituent along with several other glycosylated myricetin derivatives. During the ethnomedical application, cleavage of the aglycon can be caused by thermal treatment (boiling or roasting) [18], or by other components with β-glucosidase activity in herbal mixtures [19]. During application to skin tissue, flavonoid glycosides may also be susceptible to enzymatic hydrolysis [20].…”
Section: In-vitro Anti-inflammatory Activity Of C Collinum Aqueous Lmentioning
confidence: 99%